Bronchopneumonia in sheep associated with Providencia stuartii (Research, Society and Development, 2021)
Bacteria of the genus Providencia are opportunistic pathogens in humans, widely distributed in the environment and associated with greater resistance to antibiotics, and this being uncommon the association with clinical diseases. This study reports the isolation of P. stuartii in two sheep that presented clinical signs of pneumonia. At necropsy there was severe and acute fibrinopurulent bronchopneumonia. Histologically, there were infiltrated neutrophils and fibrin in the alveolar lumen, and the alveolar septa presented multifocal thickening with moderate proliferation of pneumocytes and mononuclear interstitial infiltrate. Providencia sp. was isolated in the microbiological tests of the lung and tracheal secretions. The isolate was subjected to DNA extraction, polymerase chain reaction (PCR) for the 16SrRNA gene and sequencing of genomic DNA, which demonstrated 100% homology with P. stuartii. This is the first report of the presence of this microorganism as a cause of interstitial and fibrinopurulent bronchopneumonia in sheep. Therefore, it is suggested that epidemiological surveillance strategies should be carried out in animals to better understand their role in the dissemination of this pathogen.